Model uncertainty in macroeconomics: On the implications of financial frictions - Michael Binder; Philipp Lieberknecht; Jorge Quintana; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
For some time now, structural macroeconomic models used at central banks have been predominantly New Keynesian DSGE models featuring nominal rigidities and forwardlooking decision-making. While these features are widely deemed crucial for policy evaluation exercises, most central banks have added more detailed characterizations of the financial sector to these models following the Great Recession in order to improve their fit to the data and their forecasting performance. We employ a comparative approach to investigate the characteristics of this new generation of New Keynesian DSGE models and document an elevated degree of model uncertainty relative to earlier model generations. Policy transmission is highly heterogeneous across types of financial frictions and monetary policy causes larger effects, on average. The New Keynesian DSGE models we analyze suggest that a simple policy rule robust to model uncertainty involves a weaker response to inflation and the output gap in the presence of financial frictions as compared to earlier generations of such models. Leaning-against-the-wind policies in models of this class estimated for the Euro Area do not lead to substantial gains. With regard to forecasting performance, the inclusion of financial frictions can generate improvements, if conditioned on appropriate data. Looking forward, we argue that model-averaging and embracing alternative modelling paradigms is likely to yield a more robust framework for the conduct of monetary policy.
urn:nbn:de:hebis:30:3-431634
Keywords: 330; model uncertainty; model comparison; New Keynesian DSGE; financial frictions; monetary policy transmission; fiscal policy transmission; macroprudential policy transmission; robust monetary policy; forecasting